Examining T-peel specimen bond length effects: Experimental and numerical explorations of transitions to steady-state debonding. (15th December 2019) - Li, Qian; Batra, Romesh C.; Graham, Ian; Dillard, David A.
Abstract: The broad versatility of the T-peel test, widely used for characterizing adhesion across a plethora of adhesives, adherends, and geometries, results in a range of responses that may complicate meaningful interpretation. This research effort, involving several specific specimen types, was undertaken to investigate concerns that commonly used configurations may not always result in plateaus in the force-displacement response. An experimental and numerical study is conducted on debonding of T-peel specimens having 75 mm bond length and 0.81 mm thick adherends made of either 6061 aluminum (Al) or one of the three steels (G70 70U hot dip galvanized, E60 elctrogalvanized (EGZ), 1010 cold-rolled steel) bonded with either LORD ® 406 or Maxlok™ acrylic adhesive. For the EGZ and the Al adherends, specimens with a bond length of 250 mm and adherend thickness of 1.60 mm are also examined. Effects of adherend materials and thicknesses, bond lengths, and adhesives on test results are examined using three metrics to interpret the T-peel bond performance. A limited correlation is found between the commonly used "T-peel strength" and the energy dissipated per unit debond area. For these two metrics, the relative performances of the CRS and the Al specimens are quite different. Quasi-static plane strain deformations of the test specimens are analyzed by the finite element method (FEM) and a cohesive zone model using the commercial software, ABAQUS, to help interpret the test data. Numerical results provided energies required to elastically and plastically deform the adherends, and help determine the transition from non-steady-state to steady-state debonding. The FE simulations also facilitate determination of the fraction of the crosshead displacement at which steady-state debonding occurs. Results reported herein could help engineers select appropriate peel specimen dimensions for extracting meaningful data for the adhesive performance and comparisons.